ACCULTURATION ELEMENTS ON SANG CIPTA RASA AND PANJUNAN RED MOSQUE - Gaputra, Agara Dama (Journal of Islamic Architecture, 2020)
Acculturation is a phenomenon of mixing up the local culture with one or more external cultures, which produces a unique new culture without leaving its original cultural identity. In architecture, acculturation can form new styles that can then develop into a more contemporary architectural form. Cirebon, as one of the geographically strategic areas, is a place where acculturation often occurs. As a city that holds a lot of history, including architecture, the mosques in Cirebon can be the forerunner of the Old Javanese Mosques throughout the Archipelago. The style of the old Cirebon mosques is the result of the acculturation of various cultures. This research explores acculturation in ancient mosques in Cirebon through the Sang Cipta Rasa Mosque and the Panjunan Red Mosque.Â  This research aims to identify acculturation in the object of study through physical element analysis. It can be seen what makes these two study objects become the "face" of the old mosque in Cirebon. Through literature review and observation, it is found that the physical elements of the two study objects were the result of a synthesis of Javanese, Islamic, Hindu-Buddhism, and Chinese architecture.